Determination of the orbital moment and crystal-field splitting in LaTiO 3 - Haverkort, Maurits W. (Physical review letters, 2005)
Utilizing a sum rule in a spin-resolved photoelectron spectroscopic experiment with circularly polarized light, we show that the orbital moment in LaTiO3 is strongly reduced from its ionic value, both below and above the Néel temperature. Using Ti L2,3 x-ray absorption spectroscopy as a local probe, we found that the crystal-field splitting in the t2g subshell is about 0.12-0.30 eV. This large splitting does not facilitate the formation of an orbital liquid.